Uma metodologia em cascata de quatro etapas para classificar códigos NCM usando técnicas de PLN - PINHEIRO, Pedro Luiz Braga (2023)
This work aims to develop a process to classify the descriptions of products present in electronic invoices (NF-e). This classification is based on the 8 digits of the Common Mercosur Nomenclature (NCM), separated into 4 parts, Chapter, Position, Subheading and item/Subitem. The classification was performed using the Support Vector Machine (SVM) algorithm and the Naıve Bayess algorithm together with Natural Language Processing (NLP) techniques, for processing a database of 340,000 different products. The data were divided into 80% training and 20% testing and an accuracy of 90% was obtained for a total of 98 classes.